The philosopher responds an intellectual correspondence from the tenth century. - Abū Ḥayyān al-Tawḥīdī, ʻAlī ibn Muḥammad, active 10th century (Library of Arabic literature., 2019)
Questions and answers from two great philosophersWhy is laughter contagious? Why do mountains exist? Why do we long for the past, even if it is scarred by suffering? Spanning a vast array of subjects that range from the philosophical to the theological, from the philological to the scientific, The Philosopher Responds is the record of a set of questions put by the litterateur Abu Hayyan al-Tawhidi to the philosopher and historian Abu 'Ali Miskawayh. Both figures were foremost contributors to the remarkable flowering of cultural and intellectual life that took place in the Islamic world during the reign of the Buyid dynasty in the fourth/tenth century. The correspondence between al-Tawhidi and Miskawayh holds a mirror to many of the debates and preoccupations of the time and reflects the spirit of rationalistic inquiry that animated their era. It also provides insight into the intellectual outlooks of two thinkers who were divided as much by their distinctive temperaments as by the very different trajectories of their professional careers. Alternately whimsical and tragic, wondering and brooding, trivial and profound, al-Tawhidi's questions provoke an interaction as interesting in its spiritedness as in its content. This new edition of The Philosopher Responds is accompanied by the first full-length English translation of this important text, bringing this interaction to life for the English reader.